Inverted S-Shaped Compact Antenna for X-Band Applications - M. Samsuzzaman; M. T. Islam (The Scientific World Journal)
A novel probe-fed compact inverted S-shaped multifrequency patch antenna is designed. By employing two rectangular slots that change the conventional rectangular patch into an inverted S-shaped patch, the antenna is able to operate in triple frequency in the X-band. The performance criteria of the proposed design have been experimentally verified by fabricating a printed prototype. The measured results show that the −10 dB impedance bandwidth of the proposed antenna at lower band is 5.02% (8.69–9.14 GHz), at middle band is 9.13% (10.47–11.48 GHz), and at upper band is 3.79% (11.53–11.98 GHz). Two elliptical slots are introduced in the ground plane to increase the peak gain. The antenna is excited by a simple probe feeding mechanism. The overall antenna dimension is  0.52λ×0.60λ×0.046λ at a lower resonance frequency of 9.08 GHz. The antenna configuration and parametric investigation are conducted with the help of the high frequency structural simulator, and a good agreement is achieved between the simulated and measured data. The stable gain, omnidirectional radiation pattern, and consistent radiation efficiency in the achieved operating band make the proposed antenna a suitable candidate for X-band applications.